Beta stability and predictability of Malaysian stock - Hoong, Tay Bee; Mohamed, Zulkifli (Penyelidikan, Pembangunan & Pengkomersilan, 2010)
Investors in general will make investment decisions based on information available in the market. In regards to this, beta coefficients are used by some investors as a forecasting tool to evaluate the investment risk. However, whether or not beta values are a good estimator of risk for a particular stock depends on its stability and predictability over time. Previous studies however reveal inconclusive results in terms of stability and predictability of beta values. This study examines the stability and predictability of beta values of one hundred stocks listed in Bursa Malaysia from the year 1998 to 2007. Beta values are computed based on Single Index Model proposed by Sharpe (1964). Stability of beta is examined based on paired observation test and risk-class membership, while predictability of betas is investigated based on correlation analysis. The study reveals that beta values are not stable during the observation period for Malaysian stocks. However, it can be predicted with confidence from those in an earlier period. The results suggest that the investors need to be careful when examine the stability of beta values for the stocks as there may be changing economic conditions which can contribute to the changing of the company profile over time. Nevertheless, investors and fund managers may still use beta as one of their risk forecasting tools as beta can be predicted with certain degree of accuracy from those in an earlier period. The results of this study will facilitate investors and fund managers in investment decision making process.